2003
DOI: 10.1177/000348940311201006
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms, Quality of Life, Videolaryngoscopy, and Twenty-Four-Hour Triple-Probe Ph Monitoring in Patients with Typical and Extraesophageal Reflux

Abstract: A prospective study was designed to characterize patients with typical and extraesophageal reflux (EER) symptoms and seek predictive patterns for each group. Fifteen subjects without symptoms, 16 patients with symptomatic gastroesophageal reflux disease (GERD), and 37 patients with symptomatic EER were evaluated with outcomes tools, videolaryngoscopy, and 24-hour triple-probe pH monitoring. Higher symptom scores, Voice Handicap Index scores, and Gastrointestinal Symptom Rating Scale scores, as well as similarl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 15 publications
4
26
0
Order By: Relevance
“…The scores in our study were in the same range as found in previous studies describing patients suffering from posterior laryngitis, and confirm that these patients have a reduced HRQOL [26][27][28]. The new finding in the present study is that the reduced scores apply to the female population and not to the male population.…”
Section: Discussionsupporting
confidence: 90%
“…The scores in our study were in the same range as found in previous studies describing patients suffering from posterior laryngitis, and confirm that these patients have a reduced HRQOL [26][27][28]. The new finding in the present study is that the reduced scores apply to the female population and not to the male population.…”
Section: Discussionsupporting
confidence: 90%
“…The median found in that study for the total VHI score was 30, not so far from the one found in the present paper (23.5 Other comparable groups found in the literature were of patients with gastroesophageal reflux disorder 19 (mean total score of 21) and patients with laryngopharyngeal reflux (29.4 and 23.1 for women and men, respectively) 21 . The total scores of patients with laryngopharyngeal reflux were 28.14 in a study led by Pribuisiene et al in 2006 20 .…”
Section: Graph 10supporting
confidence: 52%
“…VHI was used as a means to measure the voicerelated handicap in different disease groups, such as organic dysphonias 15 , presbyphonia 16 , professional use of one's voice 17,18 , gastroesophageal reflux disorder (GERD) and laryngopharyngeal reflux disorders 19,20,21 , adduction and abduction spasmodic dysphonia 22,23,24 , thyroplasties 25,26,27 , microsurgery for benign 28,29 and malignant 30,31,32 disorders, radiography for laryngeal cancer 33 , use of tracheoesophageal 34 and speech therapy 35,36 . Numerous authors compared other methods of vocal assessment.…”
Section: Introductionmentioning
confidence: 99%
“…However, other investigators failed to confirm a relation between reported symptoms and pH probe diagnosed LPR [52] and its use in children has not been validated.…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…In this study, edema and erythema of the posterior supraglottis, vocal folds or subglottis were the most useful findings for diagnosis of reflux. Powitzky et al [52] in a prospective study developed a composite score based on six laryngeal findings (pseudosulcus, ventricular obliteration, posterior commissure thickening, granulomas, arytenoids erythema, vascularity) [52]. They found that composite scores, although higher in patients compared to the asymptomatic group, did not differ significantly between GERD and LPR patients and did not correlate with the number of pathologic hypopharyngeal reflux events.…”
Section: Diagnostic Testingmentioning
confidence: 99%